May Measurement Month 2020: An Analysis of Blood Pressure Screening Results From China - Xin Chen; Li‐Ping Zhang; Xiao‐Long Wang; Ning‐Ru Zhang; Jing Yu; Li‐Ying Xu; Tong‐She Li; Hong Luan; Juan Zhang; Ya‐Min Hu; Dan Liu; Qi‐Dong Zheng; et al. (The Journal of Clinical Hypertension)
ABSTRACT We reported the blood pressure data obtained in the May Measurement Month (MMM) China project in 2020 during the COVID‐19 control period. The study participants were adults (≥ 18 years), ideally in whom blood pressure had not been measured in the previous year. Blood pressure was measured three times consecutively with a 1‐min interval in the sitting position, using a validated automated BP monitor (Omron HEM‐7081IT), and transmitted to a central database via a smartphone app. The measurement was performed at 136 sites across 29 China provinces. The 100 728 participants had a mean (±SD) age of 45.6 (±18.3) years and included 56 097 (55.7%) women. The mean systolic/diastolic blood pressure was 120.0/76.9 mm Hg. The proportion of hypertension was 28.9% (n  =  29 135), and the awareness, treatment, and control rates of hypertension were 45.3% (n = 13 212), 39.7% (n =  1573), and 24.4% (n = 7101), respectively. After adjustment for age, gender, and use of antihypertensive medication, systolic/diastolic BP were significantly higher with cigarette smoking (n = 8070, +0.5/+1.0 mm Hg, p < 0.05), mild (n = 4369, +1.2/+1.3 mm Hg, p < 0.001) and moderate or heavy alcohol drinking (n = 3871, +0.4/+0.7 mm Hg, p < 0.05), and overweight (+1.8/+1.4 mm Hg, p < 0.001) and obesity (+2.3/+1.5 mm Hg, p < 0.001). In conclusion, our study provided unique blood pressure data during the COVID‐19 period, and suggested that hypertension management might have been even more challenging when the medical professionals had to shift their focus on other urgencies.